Alkynyl-induced construction of stereodefined polysubstituted conjugated enynes via Pd-catalyzed allylic arylations. Issue 12 (12th May 2022) - Liu, Teng; Liu, Yin; Guo, Wusheng
Abstract : The alkynyl-induced construction of polysubstituted conjugated enynes with exclusive ( Z )-configurations  via  Pd-catalyzed allylic arylations is described. Abstract : The alkynyl-induced stereoselective construction of polysubstituted enynes via Pd-catalyzed allylic arylations is described. The interaction between the alkynyl group and the Pd-allyl fragment is proposed to be the key toward the desired products with exclusive ( Z )-configurations. This methodology enables the construction of a number of structurally diverse and otherwise synthetically challenging ( Z )-polysubstituted enynes under user-friendly conditions.